2000
DOI: 10.1143/jjap.39.4318
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of LixMn2O4 as Investigated by Molecular Dynamics and Density Functional Theory

Abstract: We performed density functional calculations and molecular dynamics (MD) simulations to study the structural properties of LiMn2O4. The periodic density functional calculations revealed that LiMn2O4 had a locally distorted structure due to the different local structures around Mn3+ and Mn4+. The trajectory plots of Mn3+ in Li0.4Mn2O4 at 300 K obtained by MD simulations indicated that Mn3+ ions moved easily from the 16d site, which is the original position of Mn3+ ion in the spinel st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…First-principles calculations [62,104,105,[131][132][133] can be a powerful tool for understanding atomic scale diffusion in cathode particles and providing detailed insight into diffusion mechanisms and structural properties. First-principles calculations of Li x CoO 2 diffusivity have been conducted at varying intercalation levels of Li (0 ≤ x ≤ 1), elucidating the reason for the wide variation of diffusivity based upon the activation barrier change and divacancy diffusion mechanisms (also, see Table 7) [131,134].…”
Section: Ionic Conduction In Cathode Materialsmentioning
confidence: 99%
“…First-principles calculations [62,104,105,[131][132][133] can be a powerful tool for understanding atomic scale diffusion in cathode particles and providing detailed insight into diffusion mechanisms and structural properties. First-principles calculations of Li x CoO 2 diffusivity have been conducted at varying intercalation levels of Li (0 ≤ x ≤ 1), elucidating the reason for the wide variation of diffusivity based upon the activation barrier change and divacancy diffusion mechanisms (also, see Table 7) [131,134].…”
Section: Ionic Conduction In Cathode Materialsmentioning
confidence: 99%
“…The potential function used was of Gilbert-Ida type. 34), 35) The 16d sites are assumed to be occupied by Mn III and Mn IV in equal numbers. They are distributed using the random number table before commencing the simulation (model I).…”
Section: Positional Disorder In the High-temperature Modificationmentioning
confidence: 99%
“…The lithium diffusion coefficient was measured and Monte Carlo simulations were performed to understand the lithium diffusion mechanism [2,3]. Molecule dynamics were also performed to simulate the lithium diffusion in Li x Mn 2 O 4 [4,5]. Those studies revealed that lithium diffuses in a three-dimensional network diffusion pathway within the spinel structure.…”
Section: Introductionmentioning
confidence: 99%